2013
DOI: 10.1371/journal.pone.0068709
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic S-Nitrosylation Contributes to the Counter-Regulatory Response Impairment following Recurrent Hypoglycemia

Abstract: AimsHypoglycemia is a severe side effect of intensive insulin therapy. Recurrent hypoglycemia (RH) impairs the counter-regulatory response (CRR) which restores euglycemia. During hypoglycemia, ventromedial hypothalamus (VMH) production of nitric oxide (NO) and activation of its receptor soluble guanylyl cyclase (sGC) are critical for the CRR. Hypoglycemia also increases brain reactive oxygen species (ROS) production. NO production in the presence of ROS causes protein S-nitrosylation. S-nitrosylation of sGC im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 38 publications
(71 reference statements)
1
48
2
Order By: Relevance
“…14,15,19,20,25,35 The time course and magnitude of IIH were similar with or without RH, and in this respect, our data differ from some reports in which the degree of hypoglycaemia becomes more severe with RH. 19,23 The magnitude of the elevation of plasma EPI concentration produced by acute IIH in our study is also less pronounced than reported in the literature during similar levels of hypoglycaemia in non-diabetic rats.…”
Section: Effect Of Rh On Elevation Of Counter-regulatory Hormones In contrasting
confidence: 84%
See 3 more Smart Citations
“…14,15,19,20,25,35 The time course and magnitude of IIH were similar with or without RH, and in this respect, our data differ from some reports in which the degree of hypoglycaemia becomes more severe with RH. 19,23 The magnitude of the elevation of plasma EPI concentration produced by acute IIH in our study is also less pronounced than reported in the literature during similar levels of hypoglycaemia in non-diabetic rats.…”
Section: Effect Of Rh On Elevation Of Counter-regulatory Hormones In contrasting
confidence: 84%
“…19,23 The magnitude of the elevation of plasma EPI concentration produced by acute IIH in our study is also less pronounced than reported in the literature during similar levels of hypoglycaemia in non-diabetic rats. 19,24,25,35,[51][52][53] This difference may be explained by the lower dose of insulin used to attain hypoglycaemia in our studies. As illustrated in Figure S7(a), and reported from the Beverly laboratory, 54 a similar time course of blood glucose decline can be attained using different doses of insulin, but with a lower dose, recovery towards euglycaemia begins sooner.…”
Section: Effect Of Rh On Elevation Of Counter-regulatory Hormones In mentioning
confidence: 73%
See 2 more Smart Citations
“…Recurrent Hypoglycemia is achieved due to increased insulin doses for patients with diabetes type I or may be as a result of a congenital deformity of the metabolic processes or birth defects in insulin secretion for people who have diabetes. Several previous studies showed that hypoglycemia can cause oxidative stress by increasing reactive oxygen species (ROS) which caused brain tissue injury and death [2] [3] [4] [5] or by increasing the production of lipid peroxidation products (LPO) such as MDA [6] [7] [8] and the deficiency in the activity of SOD as well as the depletion of GSH content in the crust and hippocampus areas of the brain of mice [6] [8]. Pine bark extract (PBE) has many phenolic compounds such as catechins and epicatechins with beneficial impacts for human health.PBE from the French maritime pine tree (Pycnogenol, PY); Pinus pinaster.…”
Section: Introductionmentioning
confidence: 99%